The impact of exchange rate volatility on the stock market index returns of select developed and developing Asian countries: An analysis - Alfonso, Alianne J. (Animo Repository, 2022)
The study sought to investigate the interaction among exchange rate volatility and the stock market index returns of the selected developed and developing Asian countries, namely, Japan, Singapore, India, and the Philippines. It also compared the sensitivity of the countries’ exchange rates in the listed economies. Using ARDL, long-run relationships across the countries were also examined. Monthly data sets covering the 2011-2021 period for the foreign exchange as well as stock market indices in the Japanese, Singaporean, Indian, and Philippine nations were utilized and ran using ARCH/GARCH, simple regression estimation, and the ARDL models. The ARCH statistical model prevailed over GARCH to calculate the existence of volatilities in exchange rate of these countries, hence, the results revealed that stock market performance showed a weak association with exchange rate volatility in both developed and developing economies. Hence, the outcome obtained from the simple linear regression model to measure exchange rate sensitivity to fluctuations or variance were more pronounced in developing nations compared to developed ones. These findings can be ascribed from the dependence of the forex market performance among developing economies on the currencies of the developed economies and they are less likely to hedge foreign risks compared to the latter. Contingent on the outcome obtained in the ARDL model, evidence on the significance of a long-run effect that exchange rate volatility has on the returns of the selected developed and developing Asian countries’ indices was found. The findings provide overall policy implications among national governments and supervisory bodies in the emerging markets and among investors to monitor the performance of the two financial markets.